Implementation of the Integration of Islamic Values (Akhlakul Karimah, At-Tasamuh, Ar-Rahmah, And Al-Adl) in Learning as an Effort to Prevent Bullying in Middle School Students - Nurul Widhiarto; Bambang Sumardjoko; Achmad Fathoni (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to analyze the implementation of the integration of Islamic values, including akhlakul karimah, at-tasamuh, ar-rahmah, and al-adl, in learning as an effort to prevent bullying among junior high school students. This study uses a qualitative approach with a case study design conducted at Muhammadiyah Imam Syuhodo Polokarto Junior High School. The research subjects consisted of the principal, Islamic religious education teachers, guidance counselors, homeroom teachers, and eighth-grade students. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the phenomenon of bullying among students generally occurs in the forms of verbal and physical bullying triggered by excessive joking, peer pressure, and lack of emotional control. The integration of Islamic values in learning is carried out through the habituation of Islamic behavior, strengthening moral values in learning materials, and character-building activities at school. The implementation of the values of akhlakul karimah (good character), at-tasamuh (tolerance), ar-rahmah (mercy), and al-adl (justice) has been proven to shape students’ character to become more tolerant, empathetic, and respectful of others, thereby reducing the potential for bullying. This research demonstrates that integrating Islamic values into learning can be an effective character education strategy in creating a safe and conducive school environment.